2019
DOI: 10.1055/a-0820-1053
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine needle injection of alcohol for ablation of an insulinoma: a well documented successful procedure

Abstract: A 21-year-old woman presented with recurrent hypoglycemia, syncope, and episodic seizures, associated with rapid weight gain (body mass index [BMI] 60). Hyperinsulinemia was confirmed and she was started on treatment with diazoxide. Magnetic resonance imaging showed a 1.5-cm nodule at the pancreatic head. Endoscopic ultrasound (EUS) confirmed a 1.5-cm hyperechoic nodule within the pancreatic head, between the common bile duct and the main pancreatic duct. EUS-guided fine needle aspiration (EUS-FNA) was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Body mass index was only reported in six cases. 10 , 22 , 29 , 31 , 37 , 46 In 5 female and 1 male patient, the average age was 55 (range: 21–78) years. Obesity (BMI > 40 kg/m 2 ) was recorded in four cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body mass index was only reported in six cases. 10 , 22 , 29 , 31 , 37 , 46 In 5 female and 1 male patient, the average age was 55 (range: 21–78) years. Obesity (BMI > 40 kg/m 2 ) was recorded in four cases.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that 21 out of 65 patients (32% of all cohort) had multiple co-morbidities, which precluded surgical intervention; however, EUS-guided RFA/EA was successful in them. 6 , 16 , 22 , 23 , 25 – 29 , 31 , 36 39 , 41 , 42 , 45 , 46 , 48 – 52…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent case reports and small case series have been published describing the use of EUS‐EA for both F‐PanNENs and NF‐PanNENs. Up to December 2019, 83 patients with 96 lesions have been treated by EUS‐EA20–42 (Table 2). The success rate was 94.7% for F‐PanNENs and between 50% and 62.5% for NF‐PanNENs (Table 3).…”
Section: Eus‐guided Ethanol Ablationmentioning
confidence: 99%
“…However, insulinomas are very small lesions that can be difficult to locate in the pancreas, therefore, extensive pre-and intraoperative explorations are required to optimise surgical management. As an alternative to surgery, endoscopic ultrasound-guided ablation therapies with ethanol or by radiofrequency have recently been developed, with limited available data to date [46][47][48].…”
Section: Insulinomasmentioning
confidence: 99%